Preserving Memories Together: Proposing Artifacts for Collective Digital Memorials - Monteiro, Luis Flavio Ferreira; Maciel, Cristiano; Trevisan, Daniele; Pereira, Vinícius Carvalho (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2024: Anais do XX Simpósio Brasileiro de Sistemas de Informação, 2024)
Context: In the face of technological advancements and the abundance of data generated on social networks, challenges arise in preserving post-mortem data in information systems, making the creation of digital memorials a necessity. The presence of previous theoretical studies and the absence of practical examples of these memorials underscore the demand for innovative solutions. Problem: Post-mortem data management in Information Systems faces increasing challenges for its development. Given the specificity and complexity of digital memorials, careful solution design is essential. Solution: The study proposes artifacts, including requirements, prototypes, and evaluations, for a collective digital memorial system, building upon previous recommendations and adopting theories and practices from Software Engineering. IS Theory: Regarding the types of information systems, this proposal aims to structure processes for collective digital memorials of the software type, considering them as socio-technical systems. Method: The research is applied, with a qualitative approach, involving literature reviews, artifact production for software engineering, focus group discussions, and questionnaires. Results: A set of artifacts useful for the creation of information systems in this field is proposed, including context modeling, requirements elicitation, and prototyping, which are subsequently evaluated through focus group discussions and questionnaires. The results are discussed in the article. Contributions: The study advances the development of collective digital memorials, providing practical and innovative guidelines. The artifacts contribute to the scarcity of studies on digital memorials in the Brazilian context, considering a set of previous studies conducted over years of research by experts in the field.